2001
DOI: 10.1002/1099-0682(200108)2001:8<1929::aid-ejic1929>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

The Crystal Structure of a Phosphite Ozonide, C2H5C(CH2O)3PO3

Abstract: The crystal structure of C 2 H 5 C(CH 2 O) 3 PO 3 shows that this ozonide contains a symmetric, almost planar, four-membered [a]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
8
0
3

Year Published

2003
2003
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 34 publications
0
8
0
3
Order By: Relevance
“…Equally interesting is the structure and bonding in the P 4 O 18 molecule which contains four essentially equivalent (approximate D 2 symmetry) hypercoordinate P atoms. Similar to the phosphite ozonide C 2 H 5 C(CH 2 O) 3 PO 3 , [2] the P atom in the P 4 O 18 molecule forms a distorted square pyramid arrangement with the O atoms, with the apical PÀO bonds being slightly shorter (1.59 ) than the four basal PÀO bonds (1.63-1.65 ). The O À O bond lengths in the covalently bound ozonide ligands correspond to typical OÀO single bonds (1.45 ).…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…Equally interesting is the structure and bonding in the P 4 O 18 molecule which contains four essentially equivalent (approximate D 2 symmetry) hypercoordinate P atoms. Similar to the phosphite ozonide C 2 H 5 C(CH 2 O) 3 PO 3 , [2] the P atom in the P 4 O 18 molecule forms a distorted square pyramid arrangement with the O atoms, with the apical PÀO bonds being slightly shorter (1.59 ) than the four basal PÀO bonds (1.63-1.65 ). The O À O bond lengths in the covalently bound ozonide ligands correspond to typical OÀO single bonds (1.45 ).…”
mentioning
confidence: 97%
“…However, it was not until very recently that Dimitrov and Seppelt were able for the first time to unequivocally answer the question as to whether these ozonides definitely contained a fourmembered PO 3 ring. [2] Crystal-structure analysis of C 2 H 5 C(CH 2 O) 3 PO 3 showed that this ozonide does in fact contain a symmetric, almost planar, four-membered PO 3 ring ( Figure 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Die Frage nach der Struktur der Phosphitozonide konnte allerdings erst kürzlich von Seppelt und Dimitrov beantwortet werden 2. Bis dahin war es nicht gelungen, die Existenz des vermuteten viergliedrigen PO 3 ‐Ringes eindeutig nachzuweisen.…”
unclassified
“… Molekülstruktur des ersten strukturell charakterisierten Phosphitozonids, C 2 H 5 C(CH 2 O) 3 PO 3 2…”
unclassified